Benign biliary strictures refractory to standard bilioplasty treated using polydoxanone biodegradable biliary stents: retrospective multicentric data analysis on 107 patients - Mauri, Giovanni; Michelozzi, Caterina; Melchiorre, Fabio; Poretti, Dario; Pedicini, Vittorio; Salvetti, Monica; Criado, Eva; Falcò Fages, Joan; De Gregorio, Miguel Ángel; Laborda, Alicia; Sonfienza, Luca Maria; Cornalba, Gianpaolo; et al. (European radiology, 2016)
OBJECTIVES: To assess mid-term outcome of biodegradable biliary stents (BBSs) to treat benign biliary strictures refractory to standard bilioplasty. METHODS: Institutional review board approval was obtained and patient consent was waived. 107 patients (61 males, 46 females, mean age 59 ± 16 years), were treated. Technical success and complications were recorded. Ninety-seven patients (55 males, 42 females, aged 57 ± 17 years) were considered for follow-up analysis (mean follow-up 23 ± 12 months). Fisher's exact test and Mann-Whitney U tests were used and a Kaplan-Meier curve was calculated. RESULTS: The procedure was always feasible. In 2/107 cases (2 %), stent migration occurred (technical success 98 %). 4/107 patients (4 %) experienced mild haemobilia. No major complications occurred. In 19/97 patients (18 %), stricture recurrence occurred. In this group, higher rate of subsequent cholangitis (84.2 % vs. 12.8 %, p = 0.001) and biliary stones (26.3 % vs. 2.5 %, p = 0.003) was noted. Estimated mean time to stricture recurrence was 38 months (95 % C.I 34-42 months). Estimated stricture recurrence rate at 1, 2, and 3 years was respectively 7.2 %, 26.4 %, and 29.4 %. CONCLUSION: Percutaneous placement of a BBS is a feasible and safe strategy to treat benign biliary strictures refractory to standard bilioplasty, with promising results in the mid-term period. KEY POINTS: • Percutaneous placement of a BBS is 100 % feasible. • The procedure appears free from major complications, with few minor complications. • BBSs offer promising results in the mid-term period. • With a BBS, external catheter/drainage can be removed early. • BBSs represent a new option in treating benign biliary stenosis.
Keywords: recidiva; stenty; Percutaneous transhepatic bilioplasty; Biliary Tract; Humans; Prosthesis Implantation; lidé středního věku; vstřebatelné implantáty; Female; implantace protézy; výsledek terapie; lidé; Absorbable Implants; Stents; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Treatment Outcome; Biliary Tract Diseases; Biliary stricture; Recurrence; nemoci žlučového ústrojí; retrospektivní studie; žlučové ústrojí; Percutaneous transhepatic cholangiography; mužské pohlaví; Bioabsorbable biliary stent; Constriction, Pathologic; následné studie; stenóza